Dances in Opera: St. Petersburg. (November 2015) - Wiley, Roland John
Abstract : In Russia opera dances emerged in the eighteenth century, distinguishing themselves from other theatre works that included dance; the most important works and composers of this period will be summarized. As a repertoire of continuing interest, opera dances began with those of Mikhail Glinka in 1836 and 1842. Problems of studying the opera dances since then, including local practice, faulty scholarship and press criticism, will be identified. The principal makers of opera dances in Russia are introduced next together with their accomplishments, not least in light of so-called theatre reforms of the early 1880s, which favored opera over ballet proper. Finally, selected opera dances from Glinka to Tchaikovsky are analysed, with elaborations from historical records and the contemporary press.